Complete remission of advanced hepatocellular carcinoma following transient chemoembolization and portal vein ligation - Yuki Koga; Toru Beppu; Katsunori Imai; Kunitaka Kuramoto; Tatsunori Miyata; Yuki Kitano; Shigeki Nakagawa; Hirohisa Okabe; Kazutoshi Okabe; Yo-ichi Yamashita; Akira Chikamoto; Hideo Baba (Surgical Case Reports, 2018)
Abstract Background Macroscopic diffuse-type hepatocellular carcinoma with concomitant major portal vein tumor thrombus (PVTT) and peritoneal dissemination indicates poor prognosis. Additionally, triple-positive tumor marker status is a predictor of poor outcome even after hepatectomy. Sorafenib is recommended in such patients, but it has limited therapeutic effectiveness. Case presentation A 54-year-old man was diagnosed with a liver abscess that was treated by puncture and drainage at a regional hospital. However, the diagnosis was subsequently changed to hepatocellular carcinoma with macroscopic portal vein tumor thrombus, based on the results obtained for the triple-positive tumor markers (alpha-fetoprotein, 45,928 ng/ml; protein induced by vitamin K absence or antagonist-II, 125,350 mAU/ml; and alpha-fetoprotein-L3, 38.3%). As the patient’s liver functional reserve was not adequate for curative resection, chemoembolization was performed with a hepatic arterial infusion of cisplatin (50 mg) and 5-FU (1000 mg), followed by mild embolization with cisplatin (50 mg) suspended in lipiodol (5 ml) and starch microspheres (300 mg) containing mitomycin C (4 mg). As the thrombus had progressed to the bifurcation of the right and left portal veins, the right vein was surgically ligated. Three peritoneal nodules could be identified and were removed. Three additional rounds of hepatic arterial chemotherapy/chemoembolization were performed after the initial surgery. At the 2-year evaluation, all tumor markers were observed to have normalized and diagnostic imaging showed complete remission. Conclusions Complete remission of hepatocellular carcinoma with macroscopic portal vein tumor thrombus and peritoneal dissemination was obtained with a treatment regimen that involved four rounds of hepatic arterial infusion chemotherapy and transient chemoembolization, portal vein ligation, and the removal of peritoneal dissemination. This regimen can be recommended for patients with advanced hemiliver lesions who cannot undergo curative resection.